The Removal of a Stuck Catheter: An Alternative to Hong's Technique. Issue 6 (November 2016) - Lodi, Massimo; Ebrahimi, Reza Far; Pezzotti, Piera; Carbonari, Luciano
The use of the tunneled central venous catheter (CVC) is steadily increasing worldwide as a means of vascular access for hemodialysis. The increased use of these devices, which often outlive the patients, and the extended time they are used are associated with more frequent complications. Among these, one of the emerging complications is that of the "embedded" or stuck catheter. This term refers to when the catheter cannot be removed after detaching the retention cuff. In medical literature, experiences with the removal of stuck catheters are described with the use of several different methods. Currently the most commonly used technique also considered the safest is "endoluminal dilation" also known as Hong's Technique, recently modified by Quaretti and Galli. Below, a new technique using a Vollmar ring is described for removing a stuck catheter as an alternative to Hong's technique, or after a failed attempt at using Hong's technique.